2007
DOI: 10.2527/jas.2006-063
|View full text |Cite
|
Sign up to set email alerts
|

Variance component analysis of quantitative trait loci for pork carcass composition and meat quality on SSC4 and SSC111

Abstract: In a previous study, QTL for carcass composition and meat quality were identified in a commercial finisher cross. The main objective of the current study was to confirm and fine map the QTL on SSC4 and SSC11 by genotyping an increased number of individuals and markers and to analyze the data using a combined linkage and linkage disequilibrium analysis method. A modified version of the method excludes linkage disequilibrium information from the analysis, enabling the comparison of results based on linkage infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…Our most prominent SNPs associated with meat colour a* and colour b* were on SSC4 und SSC14, respectively, where QTL were previously shown 22-23, 27-29. Further, Duthie and colleagues 21 detected a QTL for the pH of ham 24 hours post-mortem surrounding the same region of SSC14, which was also found in our study.…”
Section: Discussionsupporting
confidence: 87%
“…Our most prominent SNPs associated with meat colour a* and colour b* were on SSC4 und SSC14, respectively, where QTL were previously shown 22-23, 27-29. Further, Duthie and colleagues 21 detected a QTL for the pH of ham 24 hours post-mortem surrounding the same region of SSC14, which was also found in our study.…”
Section: Discussionsupporting
confidence: 87%
“…for the same trait ranging from 0.19 to 0.55. Regarding backfat thickness, studies using the traditional restricted maximum likelihood (REML) method observed a heritability of 0.45 (van Wijk et al 2005). However, this study found lower heritability values for this trait (0.13-0.37).…”
Section: Resultsmentioning
confidence: 99%
“…The first two QTL regions have moderate effects on meat color traits (about 0.33 STD), while the SSC13 QTL has an effect of 0.75 STD on meat lightness. Three QTL for meat quality traits were previously reported for the SSC1b, SSC4 and SSC8 regions by Ponsuksilii et al [47] and van Wijk et al [48] in crossbred populations, while the SSC1d QTL region has been shown to influence meat quality traits in Landrace pigs [49]. …”
Section: Discussionmentioning
confidence: 99%